2013
DOI: 10.5194/bg-10-2711-2013
|View full text |Cite
|
Sign up to set email alerts
|

Factors challenging our ability to detect long-term trends in ocean chlorophyll

Abstract: Global climate change is expected to affect the ocean's biological productivity. The most comprehensive information available about the global distribution of contemporary ocean primary productivity is derived from satellite data. Large spatial patchiness and interannual to multidecadal variability in chlorophyll a concentration challenges efforts to distinguish a global, secular trend given satellite records which are limited in duration and continuity. The longest ocean color satellite record comes fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 46 publications
5
82
0
Order By: Relevance
“…Moreover, advanced data assimilation techniques for real-time circulation and ecosystem models in the CC rely heavily on observational "truth" from satellite-derived chlorophyll. While we did not evaluate matchups for other coastal regions, it is likely, given that the standard algorithms are derived using a large percentage of data from the CC, that similar biases exist (e.g., [33,34]). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, advanced data assimilation techniques for real-time circulation and ecosystem models in the CC rely heavily on observational "truth" from satellite-derived chlorophyll. While we did not evaluate matchups for other coastal regions, it is likely, given that the standard algorithms are derived using a large percentage of data from the CC, that similar biases exist (e.g., [33,34]). …”
Section: Discussionmentioning
confidence: 99%
“…The newly developed extended time series include almost 20 years of data at high spatial resolution and revealed significant trends in chlorophyll concentrations. Previous studies observed varying trends in global average chlorophyll concentrations, with reports of a general decline (e.g., Behrenfeld et al, 2006;Vantrepotte and Mélin, 2009;Boyce et al, 2014;Lorenzoni et al, 2017), as well as no detectable trends (Beaulieu et al, 2013) or even a global increase of 4.13% (Gregg et al, 2005). However, there is general consensus in that there is high global variability, with regions of increasing and decreasing trends.…”
Section: Trends In Large Marine Ecosystemsmentioning
confidence: 98%
“…Blending in-situ and satellite observations of TCHLa (e.g. AMT and SeaWiFS) may lead to more robust estimates of trends (Aiken et al, 2009;Gregg & Casey, 2010;Gregg & Rousseaux, 2014) and minimise the impact of periods of missing data (Beaulieu et al, 2013;Racault et al, 2014a).…”
Section: Trends In Total Chlorophyll-amentioning
confidence: 99%